Development of hepatitis C virus vaccines: challenges and progress - Stoll-Keller, Françoise (Future Drugs Ltd, 2009)
Development of an effective vaccine against hepatitis C virus (HCV) has long been defined as a difficult challenge due to the considerable variability of this RNA virus and the observation that convalescent humans and chimpanzees could be re-infected after re-exposure. On the other hand, progress in the understanding of antiviral immune responses in patients with viral clearance has elucidated key mechanisms playing a role for control of viral infection. Studies investigating prophylactic vaccine approaches in chimpanzees have confirmed that the induction and maintenance of strong helper and cytotoxic T cell immune responses against multiple viral epitopes is necessary for protection against viral clearance and chronic infection. A multispecific B cell response resulting in rapid induction of cross-neutralizing antibodies may assist cellular responses. Therapeutic vaccination formulations currently evaluated in clinical phase are facing the fact that the immune system of chronic carriers is impaired and need the restoration of T cells functions to enhance their efficacy.